The hunchback of Notre Dame - Hugo, Victor, 1802-1885.; Cobb, Walter J.; Robb, Graham (New York : Signet Classics, 2010)
The tale of Quasimodo, the hunchbacked bellringer of Notre Dame Cathedral, and his struggles to save the beautiful gypsy dancer Esmeralda from being unjustly executed.
Includes bibliographical references (p. 509-510).
Keywords: Notre-Dame de Paris (Cathedral) -- Fiction; People with disabilities -- Fiction; France -- History -- Louis XI, 1461-1483 -- Fiction; Paris (France) -- History -- To 1515 -- Fiction; Romances